Legal Protection for Traditional Market Traders in the Face of Competition with Modern Retailers - Suaib, Sri Olawati; Moha, Sri Wahyuni S.; Tunggati, Melki T. (International Journal of Business, Law, and Education, 2025)
Traditional markets play an important role in the Indonesian economy, especially in supporting micro, small and medium enterprises (MSMEs). However, in recent decades, the existence of traditional markets has been increasingly threatened by the expansion of modern retailers that offer more competitive prices, shopping convenience, and attractive promotions. This competitive imbalance raises legal issues related to the protection of traditional market traders so that they can continue to compete fairly. Therefore, this study aims to examine existing legal arrangements and challenges in their implementation to protect traditional market traders. This research uses a normative legal research method, which focuses on analyzing relevant laws and regulations, such as Presidential Regulation No. 112/2007, Law No. 5/1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, and various Regional Regulations (Perda) that regulate zoning and licensing of modern retail. In addition, this study also examines various concrete cases that reflect the weak implementation of legal protection for traditional market traders. The results show that although regulations have regulated the protection of traditional market traders, their implementation still faces various obstacles, such as weak supervision, lack of sanctions against zoning violations, and lack of support in modernizing traditional markets. Therefore, it is necessary to strengthen policies, improve supervision, and provide incentives for traditional market traders in order to survive in the midst of competition with modern retailers. With more effective legal protection, it is expected that traditional markets can still contribute to the national economy and the welfare of the community.